The phylogenetic position of Nyctiphruretus acudens, a parareptile from the Permian of Russia - SäiIä, L. K. (Journal of Iberian Geology, 2011)
Several specimens preserving the cranial structure of Nyctiphruretus acudens, a parareptile from the Permian Mezen River locality, Rusia, are described here for the first time. Previous studies have offered conflicting reconstructed images of Nyctiphruretus but no illustrations of actual specimens. The new information was incorporated into two existing analyses of parareptilian relationships. The results indicate that Nyctiphruretus is closely related to procolophonoids, pareiasaurs and other non-pareiasaurian Mezen River parareptiles but the interrelationships within this group remain unresolved. Nyctiphruretus was recovered either as the sister taxon of a clade formed of pareiasaurs and the other non-pareiasaurian Mezen River parareptiles, or as the sister taxon of procolophonoids. This is the first time the Nyctiphruretus-Procolophonoidea clade received support in a phylogenetic analysis. The interrelationships between several other groups within the Parareptilia also remain unresolved, or poorly supported, highlighting the need for more detailed descriptions and analyses of this enigmatic group of extinct reptiles.